Penilaian Capital Asset Pricing Model (CAPM) Terhadap Tingkat Pengembalian Saham Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia - Rahmawaty Arifiani; Nafiah Nur Khalishah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Seeing the promising profit potential in the pharmaceutical sector, investors are starting to try to get profitable investment opportunities. However, investing in pharmaceutical company stocks is also not free from risk. This study aims to assess the feasibility of investing in pharmaceutical sub-sector stocks by comparing the expected return results using the Capital Asset Pricing Model (CAPM) equilibrium model and actual returns that provide investors with an understanding of the relationship between systematic risk and expected return. The method used is quantitative descriptive by processing secondary data from publications of the Indonesia Stock Exchange (IDX), Yahoo Finance and Bank Indonesia. The stocks of the companies studied are companies that have complete historical stock price data and are listed on the Indonesia Stock Exchange without delisting from July 2021-June 2024. The results of this study reveal that out of 9 company samples, there are 4 efficient stocks with a feasible category, namely KLBF, MERK, TSPC, and SOHO because E(Ri)<Ri. So the most appropriate decision for investors regarding these stocks is to buy stocks and hold them and then sell them when the price goes up again to make a profit.